Titanium surface modification by oxidation for biomedical application - Abdullah, Hasan Z. (2010)
Surface modification is a process that is applied to the surfaces of titanium substrates in order to improve the biocompatibility after implanting in the body. Two methods were used in the present work: Anodisation and gel oxidation. Anodisation was performed at room temperature in strong mineral acids (sulphuric acid (H2SO4) and phosphoric acid (H3PO4)), an oxidising agent (hydrogen peroxide (H2O2)), mixed solutions of the preceding three, and a weak organic acid mixture (β-glycerophosphate + calcium acetate). The parameters used in anodisation were: Concentrations of the electrolytes, applied voltage, current density, and anodisation time. Gel oxidation was carried out by soaking titanium substrates in sodium hydroxide (NaOH) aqueous solutions at different concentrations (0.5 M, 1.0 M, 5.0 M, and 10.0 M) at 60°C for 24 h, followed by oxidation at 400°, 600°, and 800°C for 1 h. Conceptual models representing changes in the microstructure as a function of the experimental parameters were developed using the anodisation data. The relevant parameters were: Applied voltage, current density, acid concentration, and anodisation time: • The model for anodisation using the strong acid (H2SO4) illustrates the growth rate of the film, identification of the threshold for the establishment of a consistent microstructure, and prediction of the properties of the film. • For the oxidising agent (H2O2), two models were developed: Current-control and voltage-control, the applicability of which depends on the scale of the current density (high or low, respectively). These models are interpreted in terms of the coherency/incoherency of the corrosion gel, arcing, and porosity. • The model for the strongest acid (H3PO4) is similar to that of H2O2 in current-control mode, although this system showed the greatest intensity of arcing and consequent pore size. • Anodisation in mixed solutions uses Ohm’s law to explain four stages of film growth in current-control mode. These stages describe the thickness of the gel, its recrystallisation, and the achievement of a consistent microstructure. • Anodisation in weaker organic acids allows the most detailed examination of the anodisation process. Both current density and voltage as a function time reveal the nature of the process in six stages: (1) instrumental response, (2 and 3) gel thickening, (4) transformation of the amorphous gel to amorphous titania, (5) recrystallisation of the amorphous titania, and (6) subsurface pore generation upon establishment of a consistent microstructure. Gel oxidation was done at low and high NaOH concentrations followed by oxidation. Three models were developed to represent the gel oxidation process: (1) Low concentration, (0.5 M and 1.0 M NaOH), (2) Medium concentration (5.0 M NaOH), and (3) high concentration (10.0 M NaOH). For the low concentrations with increasing temperature, the model involves: (1) amorphous sodium titanate forms over a layer of amorphous anatase and (2) a dense layer of rutile forms. For the high concentrations with increasing temperature, the model involves: (1) amorphous sodium titanate forms over a layer of amorphous anatase, (2) a dense layer of anatase forms and raises up the existing porous anatase layer, and (3) the dense and porous anatase layers transform to dense and porous rutile layers, respectively. The main difference between the two is the retention of crystalline sodium titanate in the higher NaOH concentration. Anodised and gel oxidised samples subsequently were soaked in simulated body fluid in order to study the precipitation of hydroxyapatite in the absence and presence of long UV irradiation, which has not been investigated before. With the anodised surfaces, the porous and rough titania coating facilitated both the precipitation of hydroxyapatite and the attachment of bone-like cells. UV irradiation showed greatly enhanced hydroxyapatite precipitation, which is attributed to its photocatalytic properties. With the gel oxidised surfaces, the greatest amount of hydroxyapatite precipitation occurred with the presence of both anatase and amorphous sodium titanate. Rutile suppressed precipitation.